European Union foreign and security policy : towards a neighbourhood strategy - Dannreuther, Roland (Routledge, 2004)
This book examines the degree to which the European Union has responded as a coherent and strategic actor towards the developmental and security needs of its immediate neighbourhood in the post-Cold War era.